Stemmen: het geheim van het Koninklijk Concertgebouworkest - Wel, Judith van der 1984- (Amsterdam Querido, 2015)
Insight into the ins and outs of the Concertgebouw Orchestra during its anniversary tour across five continents, covering logistics, repertoire, facts and stories from orchestra members.
Keywords: Koninklijk Concertgebouworkest (Amsterdam, Netherlands); Music history; Orchestra; Travel; Musician; Birthday; Amsterdam (Netherlands)